Assessment of Useful Alien Plant Species Cultivated and Managed in Rural Home Gardens of Limpopo Province, South Africa. (28th April 2020) - Silas Semenya, Sebua; Maroyi, Alfred
Abstract : Several communities in developing countries derive substantial part of their livelihood needs from alien plants cultivated and managed in home gardens. The aim of this study was to assess useful alien plant species cultivated and managed in home gardens of Limpopo province in South Africa. Semistructured interviews, personal observation, and guided walks with 300 participants between January 2015 and December 2016 were employed to obtain data on names of alien plants cultivated in home gardens and their use categories. A total of 101 plant species belonging to 44 families were recorded from the study area. More than half of the species (66.3%) belonged to 14 families, Fabaceae, Asteraceae, Rosaceae, Solanaceae, Lamiaceae, Anacardiaceae, Poaceae, Amaranthaceae, Apocynaceae, Brassicaceae, Cactaceae, Euphorbiaceae, Moraceae, and Myrtaceae. Twenty-six use categories of alien plants were identified in this study with the majority of species (75.2%) used for medicinal purposes, followed by ornamental (33.7%), edible fruits (24.8%), spices (16.8%), vegetables (16.8%), shade (11.9%), beverages (10.9%), construction materials (8.9%), firewood (7.9%), and hedge (7.9%). These findings corroborate the existing body of knowledge emphasizing the importance of plants grown and managed in home gardens to the livelihood needs of local communities.